Measurements of trees in the city of Abha using lidar technology by smart phones - Al-Shahrani, Eman Saeed; Al-Safi, Sulafa Haj (Journal of natural sciences, life and applied sciences, 2023)
The research aims to find an alternative, low-cost method for measuring trees and characterizing their structure using LIDAR technology carried by the iPhone 13 Pro Max, because of its importance in monitoring and inventorying large areas of gardens and providing solutions to many problems that may face those responsible for forests, such as inventorying them and how to monitor and supervise them. on large areas with a small number of employees using this technology. Advancements in smart devices (phone/tablet) and sensor technologies used in applications have paved the way for the use of smart mobile devices in various fields beyond their basic functions. For example, lidar systems are shrinking in size and these sensors are beginning to be integrated into smart communication platforms. The study concluded that this technology can be used easily and without any cost or effort, to identify trees and know all their details and information. The height of the trees in the photography area is about 3 meters, and the area of trees in the area is about 37.42 square meters. The study recommended the need to move towards the use of LIDAR technology for measuring trees and forests in general and characterizing their structures and taking care of trees and knowing the extent of their health and prosperity in the Jabal Al-Souda region, to preserve the environment and climate changes. The study also recommended paying attention to using LIDAR technology and applying it to all parks in the city of Abha and carrying out many studies that use technology and work with it on all phenomena such as roads, streets, houses, etc. in the city of Abha to identify the problems of each phenomenon.